Factors Affecting the Environment and Work Competencies in Improving Employee Performance at PT. Source of Bintang Rezeki Semarang - Zebua, Murnikasi; Rahmad Satato, Yuniarto (Jurnal Ilmiah Sumber Daya Manusia, 2025)
Employee performance is a key factor for company success in achieving organizational goals, especially in the labor-intensive garment industry. This study aims to analyze the influence of work environment and work competence on employee performance at PT. Source of Bintang Rezeki Semarang. The research method uses a quantitative approach with an explanatory survey design. The research population consists of all employees of PT. Sumber Bintang Rezeki Semarang totaling 120 people with a sample of 92 respondents determined using the Slovin formula. The sampling technique uses proportionate stratified random sampling. Data were collected through structured questionnaires with a Likert scale of 1-5 and analyzed using multiple linear regression. The results show that work environment has a positive and significant effect on employee performance (β=0.342, p=0.000), work competence has a positive and significant effect on employee performance (β=0.485, p=0.000), and both variables simultaneously have a positive and significant effect on employee performance (F=42.378, p=0.000) with the ability to explain variance of 54.4%. Work competence has a more dominant influence than work environment on employee performance. This study provides implications that companies need to prioritize employee competence development through continuous training programs while paying attention to work environment improvements to achieve optimal performance improvement.